Development and implementation of IT products - Lukianchuk, Iurii (Lutsk: LNTU, 2026)
These lecture notes provide a comprehensive guide for bachelor's level students on the end-to-end process of developing and implementing IT products. The first module covers fundamental concepts, including various development methodologies (Waterfall, Agile, Scrum), team building, system architecture, and the creation of competitive business models. The second module shifts focus to market implementation, exploring client acquisition strategies, sales funnels, and the critical analysis of unit economics for sustainability. A significant portion is dedicated to navigating international markets, with detailed insights into the regulatory and cultural specifics of the EU, USA, and Asia for Ukrainian projects. Finally, the notes offer practical guidance on securing financial resources, covering everything from crafting grant proposals and managing investor communications to understanding venture capital and alternative funding sources.
Keywords: IT products; software development lifecycle (SDLC); project management; Agile; Waterfall; business model canvas; unit economics; market entry; international markets (EU; USA; Asia); fundraising; grants; venture capital; product launch.